Pancreas-sparing, ampulla-preserving duodenectomy for major duodenal (D1–D2) perforations. Issue 11 (19th July 2018) - Di Saverio, S; Segalini, E; Birindelli, A; Todero, S; Podda, M; Rizzuto, A; Tugnoli, G; Biondi, A
Abstract: Background: Ideal surgical treatment for acute duodenal injuries should offer a definitive treatment, with low morbidity and mortality. It should be simple and easily reproducible by acute care surgeons in an emergency. Duodenal injury, due to major perforated or bleeding peptic ulcers or iatrogenic/traumatic perforation, represents a surgical challenge, with high morbidity and mortality. The aim was to review definitive surgery with pancreas-sparing, ampulla-preserving duodenectomy for these patients. Methods: Pancreas-sparing, ampulla-preserving D1–D2 duodenectomy was used for patients presenting with major duodenal injuries over a 5-year interval. The ampulla was identified and preserved using a transcystic/transpapillary tube. The outcomes were recorded. Results: Ten patients were treated with this technique; seven had perforated or bleeding peptic ulcers, two had iatrogenic perforations and one blunt abdominal trauma. Their mean age was 78 (range 65–84) years. Four patients were haemodynamically unstable. The location of the duodenal injury was always D1 and/or D2, above or in close proximity to the ampulla of Vater. The surgical approach was open in nine patients and laparoscopic in one. The mean duration of surgery was 264 (range 170–377) min. All patients were transferred to the ICU after surgery (mean ICU stay 4·4 (range 1–11) days), and the overall mean hospital stay was 17·8 (range 10–32) days. Six patients developed major postoperative complications: cardiorespiratory failure in five and gastrointestinal complications in four. Surgical reoperation was needed in one patient for postoperative necrotizing and bleeding pancreatitis. Two patients died from their complications. Conclusion: Pancreas-sparing, ampulla-preserving D1–D2 duodenectomy for emergency treatment of major duodenal perforations is feasible and associated with satisfactory outcomes. Abstract : Useful option